2018
DOI: 10.1038/s41388-018-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

GABPA inhibits invasion/metastasis in papillary thyroid carcinoma by regulating DICER1 expression

Abstract: The ETS family transcription factor GABPA is suggested as an oncogenic element, which is further supported by the recent reporting of it as the sole ETS member to activate the mutant TERT promoter in thyroid carcinomas (TC). However, it remains unclear how GABPA contributes to TC pathogenesis. The present study is designed to address this issue. TERT expression was significantly diminished in TERT promoter-mutated TC cells upon GABPA inhibition. Surprisingly, GABPA depletion led to robustly increased cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 47 publications
6
86
1
Order By: Relevance
“…Despite significantly diminished TERT expression in mutant TERT promotercarrying BC cells upon GABPA knockdown, these cells exhibited augmented proliferation, stemness, and invasive capacities, indicating that GABPA itself has a predominant role in suppressing BC aggressive state independently of TERT expression. This same scenario was recently observed in TC cells, too [46]. However, Mancini et al [25] showed that mutant TERT promoter-harboring glioblastoma cells exhibited decreased TERT expression coupled with impaired proliferation upon GABPB1L depletion within 48 h and longer incubation time triggered telomere shortening/dysfunction and attenuated tumorigenic ability of these cells.…”
Section: Discussionsupporting
confidence: 66%
“…Despite significantly diminished TERT expression in mutant TERT promotercarrying BC cells upon GABPA knockdown, these cells exhibited augmented proliferation, stemness, and invasive capacities, indicating that GABPA itself has a predominant role in suppressing BC aggressive state independently of TERT expression. This same scenario was recently observed in TC cells, too [46]. However, Mancini et al [25] showed that mutant TERT promoter-harboring glioblastoma cells exhibited decreased TERT expression coupled with impaired proliferation upon GABPB1L depletion within 48 h and longer incubation time triggered telomere shortening/dysfunction and attenuated tumorigenic ability of these cells.…”
Section: Discussionsupporting
confidence: 66%
“…However, a key challenge is how to translate these findings into a telomerase-based therapeutic strategy. The ETS family member GABPB1, required for the TERT transcription in TERT promoter-bearing glioblastoma cells, has been proposed as a target for glioblastoma treatment [56], but our results showed that inhibiting GABPA or GABPB1 robustly increased invasiveness of TC cells despite significant downregulation of TERT expression [59]. Likely, the GABPA/B function is context-dependent.…”
Section: Discussionmentioning
confidence: 57%
“…Surprisingly, however, our results obtained from thyroid cancer (TC) studies question it as a therapeutic target [59]. First, GABPA depletion leads to significant downregulation of TERT expression in TC-derived cells independently of TERT promoter mutations; Second, GABPA expression is negatively correlated with TERT expression in primary tumors from TC patients; Third, GABPA depletion robustly increases thyroid cancer cell invasion despite a diminished TERT expression.…”
Section: The Tert Gene and Its Promoter And Transcriptsmentioning
confidence: 86%
“…Intriguingly, it was recently reported that GABPA controls the cell cycle and induces cell differentiation, thus acting as a tumor suppressor regulating cell proliferation, stemness, and adhesion. It decreased tumor invasiveness and distal metastases in PTC, HCC, and bladder carcinoma [154][155][156]. GABPA levels were decreased and even negatively associated with TERT expression in PTC [154][155][156].…”
Section: Discussionmentioning
confidence: 93%
“…It decreased tumor invasiveness and distal metastases in PTC, HCC, and bladder carcinoma [154][155][156]. GABPA levels were decreased and even negatively associated with TERT expression in PTC [154][155][156]. One possible explanation is that other Ets/TCF family transcription factors bind TERTp mutations.…”
Section: Discussionmentioning
confidence: 99%